Differences between race and sex in measures of hip morphology: a population-based comparative study. Issue 2 (February 2020) - Edwards, K.; Leyland, K.M.; Sanchez-Santos, M.T.; Arden, C.P.; Spector, T.D.; Nelson, A.E.; Jordan, J.M.; Nevitt, M.; Hunter, D.J.; Arden, N.K.
Summary: Objective: This paper aims to (i) identify differences in measures of hip morphology between four racial groups using anteroposterior (AP) hip x-rays, and (ii) examine whether these differences vary by sex. Methods: 912 hip x-rays (456 individuals) from four racial groups (European Caucasians, American Caucasians, African Americans and Chinese) were obtained. Males and females (45–75 years) with no radiographic hip OA (Kellgren and Lawrence < Grade 2 or Croft < Grade 1) were included. Eleven features of hip joint morphology were analysed. Linear regression with generalised estimating equations (GEE) was used to determine race and sex differences in hip morphology. Post-hoc Bonferroni procedure was used to adjust for multiple comparisons. Results: The final analysis included 875 hips. Chinese hips showed significant differences for the majority of measures to other racial groups. Chinese were characterised by more shallow and narrow acetabular sockets, reduced femoral head coverage, smaller femoral head diameter, and a lesser angle of alignment between the femoral neck and shaft. Variation was found between other racial groups, but with few statistically significant differences. The average of lateral centre edge angle, minimum neck width and neck length differed between race and sex ( p -value for interaction < 0.05). Conclusions: Significant differences were found in measures of morphology between Chinese hips compared to African Americans or Caucasian groups; these may explain variation in hip OA prevalence rates between these groups and the lower rate of hip OA in Chinese. Sex differences were also identified, which may further explain male-female prevalence differences for OA.